STUDENT RESILIENCE FROM POOR FAMILY IN ONLINE LEARNING STUDY - Muhammad Jufri; A. Nurul Mutmainnah; Nur Atika (Balai Penelitian dan Pengembangan Agama Makassar, 2022)
Online learning for some Indonesian people experiences many problems. Various problems, such as unsupported regional signals, not being able to use technology, and so on. Here, online learning requires knowledge capabilities and supporting facilities. Lecturers and students are required to have learning tools that support being able to go online, and students must have a minimum connecting device for mobile phones and quotas to study online at home. In addition, areas in remote areas do not yet have an internet signal, to the inability of parents to buy cellphones and quotas because of poverty. For poor families, have a burden and become a problem for online learning activities. In this case, the research further explains the power and efforts of students both socially and economically in supporting online learning activities during the pandemic. Research will be conducted using a descriptive quantitative research method approach. Selection of respondents was carried out by purposive sampling. The Amount of the respondents are 30 people. The resilience of students from poor families is showed by looking for work to help the family’s economy and looking for a UKT (Single Tuition Fee) deduction facility. the GPA (Gradual Achievement Index) of students during the pandemic did not change significantly or remained at 45 percent. However, the most unfortunate thing is that the students who experienced the least increase in their GPA scores were only 16 percent. This shows that there is no significant increase in student GPA scores during the pandemic.